Polyp size measurement during colonoscopy using a virtual scale: variability and systematic differences - van Bokhorst, Querijn N. E.; Houwen, Britt B. S. L.; Hazewinkel, Yark; van der Vlugt, Manon; Beaumont, Hanneke; Grootjans, Joep; van Tilburg, Arjan; Fockens, Paul; Bossuyt, Patrick M. M.; Dekker, Evelien; on behalf of the SCALE EYE study group; Adriaanse, Marlou P. M.; Bastiaansen, Barbara A. J.; van Beurden, Yvette H.; Bronzwaer, Maxime E. S.; Hens, Brecht W. E.; Hubers, Lowiek M.; Kramer, Gem M.; Lekkerkerker, Selma J.; Meijer, Berrie; Ponds, Fraukje A.; Ramsoekh, Dewkoemar (Endoscopy, 2024)
Background Accurate polyp size measurement is important for polyp risk stratification and decision-making regarding polypectomy and surveillance. Recently, a virtual scale (VS) function has been developed that allows polyp size measurement through projection of an adaptive VS onto colorectal polyps during real-time endoscopy. We aimed to evaluate the VS in terms of variability and systematic differences.Methods We conducted a video-based study with 120 colorectal polyps, measured by eight dedicated colorectal gastroenterologists (experts) and nine gastroenterology residents following endoscopy training (trainees). Three endoscopic measurement methods were compared: (1) visual, (2) snare and (3) VS measurement. We evaluated the method-specific variance (as measure of variability) in polyp size measurements and systematic differences between these methods.Results Variance in polyp size measurements was significantly lower for VS measurements compared to visual and snare measurements for both experts (0.52 vs. 1.59 and 1.96, p < 0.001) and trainees (0.59 vs. 2.21 and 2.53, p < 0.001). VS measurement resulted in a higher percentage of polyps assigned to the same size category by all endoscopists compared to visual and snare measurements (experts: 69 % vs. 55 % and 59 %; trainees: 67 % vs. 51 % and 47 %) and reduced the maximum difference between individual endoscopists regarding the percentage of polyps assigned to the ≥ 10 mm size category (experts: 1.7 % vs. 10.0 % and 5.0 %; trainees: 2.5 % vs. 6.7 % and 11.7 %). Systematic differences between methods were < 0.5 mm.Conclusions Use of the VS leads to lower polyp size measurement variability and more uniform polyp sizing by individual endoscopists compared to visual and snare measurements.